Respuesta :
Answer:
x³ -x²-30x+72
Step-by-step explanation:
→ ( x - 3 ) ( x - 4 ) ( x + 6 )
[ expand and open brackets ]
→ ( x² -4x -3x + 12 ) ( x + 6 )
[ simplify ]
→ ( x² -7x + 12 ) ( x + 6 )
[ expand ]
→ x³ +6x² -7x² - 42x + 12x + 72
[ simplify/ final answer ]
→ x³ -x² -30x +72
[tex](x-3)(x-4) (x + 6)[/tex]
[expand and open brackets ]
[tex]→(x² -4x -3x + 12 ) ( x + 6)[/tex]
[simplify]
[tex]→(x² -7x + 12) (x+6)[/tex]
[expand]
[tex]→x³ +6x² -7x² - 42x + 12x + 72[/tex]
[simplify/final answer ]
[tex]→x³ -x² -30x +72[/tex]